Challenges of the pharmacist in the care of patients contaminated by COVID-19 in drugstores (Research, Society and Development, 2021)
COVID-19 is caused by the SARS-CoV-2 coronavirus, which generates respiratory infection, it was discovered in December 2019 in the city of Wuhan, China. In February 2020, Brazil had the first connection with the virus and after this contact began – if a change in the population's routine, hygiene measures and changes in habits were adopted to prevent the proliferation of COVID–19 in our country. Drugstores had to adapt safety standards to receive these patients because the pharmacist and his work team were on the front line and had to protect themselves from contamination. The study aims to show the challenges of the pharmacist in caring for patients contaminated by COVID. This is a narrative literature review where Google Academic databases and Virtual Health Library were consulted using the following descriptors: COVID; drugstores; pharmacists. These analyzes were carried out in the period from 2016 to 2021, consulting dissertations, theses and course completion papers. Most articles were published in 2020. It is concluded that pharmacists must carry out preventive measures in drugstores to protect their staff and population against this invisible virus.